Model Strategi Pengembangan Wisata Air Kalimeri Waterpark Di Desa Sempalwadak Kabupaten Malang - Fadilatul Qodriyah; Karina Ega Nirwana (Jurnal Aplikasi Bisnis, 2026)
This study aims to develop a strategic model for the development of Kalimeri Waterpark, located in Sempalwadak Village, Malang Regency, with the objective of enhancing the competitiveness and sustainability of the tourism sector. The method used in this study is a qualitative approach, with data collected through observation, interviews, and documentation. The population of this study includes all parties involved in tourism management and utilization, while the sample consists of managers, staff, and visitors. Data was analyzed using the SWOT method applied through the IFE Matrix, EFE Matrix, and SWOT quadrants. The findings of the study indicate that Kalimeri Waterpark has great potential in terms of attractions and basic facilities, but still faces several challenges such as a lack of innovation in rides, suboptimal utilization of facilities, and a lack of effectiveness in promotion. Opportunities for development are driven by growing interest in water tourism and the potential for community collaboration, while threats stem from the presence of similar competitors and unpredictable weather conditions. Strategic recommendations include improving the quality and variety of rides, optimizing facility usage, strengthening promotional efforts, and developing tourism programs to stabilize visitor